Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Intervening - Dewi, Sri; Hermiati, Novi Fitria (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The development of technology and science can play an important role in the quality of human resources in a company or organization. Human resources in a company are the most important part in playing the role of the company's operational activities. This study aims to analyze how the influence of Work Discipline and Work Environment on Employee Performance with Job Satisfaction as Intervening at PT. Sumber Alfaria Trijaya Tbk in North Cikarang Area. The sample in the study used a simple random sampling method and used the slovin formula. This research is included in quantitative research with a descriptive approach method. The data analysis technique uses Outer Model Analysis (Path Outer Model, Validity Test (Covergent Validity, Discriminant Validity), Reliability Test), Inner Model Analysis Test, Hypothesis Test. The results of this study are Work Discipline has a significant effect on Job Satisfaction, Work Discipline has a significant effect on Employee Performance, Job Satisfaction has a significant effect on Employee Performance, Work Environment has a significant effect on Job Satisfaction, Work Environment has no significant effect on Employee Performance, Work Discipline before being mediated by Job satisfaction has a significant effect on Employee Performance, Work Environment before being mediated by Job satisfaction has no significant effect on Employee Performance.